2014
DOI: 10.3201/eid2010.130782
|View full text |Cite
|
Sign up to set email alerts
|

Lyme Disease, Virginia, USA, 2000–2011

Abstract: Geographic expansion of Ixodes scapularis ticks has increased human exposure to Borrelia burgdorferi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…Given the lack of systematic surveillance for I. scapularis , one might ask if the range expansion suggested by our data is real or merely an artifact of enhanced tick surveillance and research activities in some areas. A true range expansion of I. scapularis in northern states, as described in this report, is supported by the largely concordant changes in the distribution of human Lyme disease cases captured through mandatory reporting of the disease since 1991 (Rand et al 2007, Raizman et al 2012, Lee et al 2013, Serra et al 2013, Brinkerhoff et al 2014, Robinson et al 2014, Wang et al 2014, Kugeler et al 2015, Mead 2015). Moreover, as detailed later in the text, true range expansions of I. scapularis have been documented in some areas where tick surveillance was conducted routinely during the period of emergence, or where extensive surveys were conducted at discrete time-points spanning periods from when the tick was absent through invasion and establishment.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Given the lack of systematic surveillance for I. scapularis , one might ask if the range expansion suggested by our data is real or merely an artifact of enhanced tick surveillance and research activities in some areas. A true range expansion of I. scapularis in northern states, as described in this report, is supported by the largely concordant changes in the distribution of human Lyme disease cases captured through mandatory reporting of the disease since 1991 (Rand et al 2007, Raizman et al 2012, Lee et al 2013, Serra et al 2013, Brinkerhoff et al 2014, Robinson et al 2014, Wang et al 2014, Kugeler et al 2015, Mead 2015). Moreover, as detailed later in the text, true range expansions of I. scapularis have been documented in some areas where tick surveillance was conducted routinely during the period of emergence, or where extensive surveys were conducted at discrete time-points spanning periods from when the tick was absent through invasion and establishment.…”
Section: Discussionsupporting
confidence: 66%
“…Review of Lyme disease and I. scapularis surveillance reports (see references in Table 2) suggests that the tick is expanding westward across the state, with highly Lyme disease endemic counties still focused in the eastern panhandle. Similarly, in Virginia, I. scapularis was considered established primarily in eastern coastal counties previously (Dennis et al 1998), but the current survey shows the tick to now be established throughout most of Virginia, with the highest densities of openly host-seeking ticks occurring in higher elevation sites (Brinkerhoff et al 2014, Kelly et al 2014). The spread of openly host-seeking I. scapularis appears to have proceeded in a southwesterly direction in Virginia, concordant with the expanding geographic distribution of Lyme disease cases and increasing incidence in Virginia (Brinkerhoff et al 2014, Lantos et al 2015).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…First, ticks from Pearisburg, VA, had the highest burden of Borrelia, and the burden was higher than that of ticks from the Northeast, all of which were confirmed to harbor B. burgdorferi sensu stricto. Lyme disease is endemic in the Northeast but has only recently emerged in the part of Virginia where Pearisburg is located (45). Second, ticks from only 5 sites had light Rickettsia burdens (Ͻ20%), and ticks from 3 of these sites were heavily infected with members of the family Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…Further research could also explore other environmental variables such as humidity, temperature, and rainfall that could be important indicators for Lyme disease emergence. Brinkerhoff et al (2014) report that human Lyme disease is present at higher elevations in Virginia than anticipated, while Diuk-Wasser et al (2012) found that low elevations, low levels of vapor pressure deficits, and small extremes in minimum temperature were correlated with the presence of nymphs infected with B. burgdorferi in a study across the eastern United States. Estrada-Peña (2002) also reports on the importance of climate variability, particularly increased winter temperatures and higher rainfall, to the creation of suitable habitat for Ixodes scapularis.…”
Section: Future Researchmentioning
confidence: 97%